Management of temporomandibular disorder associated with bruxism - Bedi S; Sharma A (Wolters Kluwer Medknow Publications, 2009)
Bruxism is the non-functional clenching or grinding of the teeth that may occur during sleep or, less commonly in the daytime in 5-20% of adults and about 30% of 56 year old children. Although research on bruxism is extensive, its etiology remains debatable. There is some literature to suggest that bruxism is correlated with temporomandibular disorders (TMDs) and malocclusion. The aim of this article is to present the course of this condition in a case of bruxism coupled with TMD with special emphasis on the importance of accurate diagnosis of maxillofacial pain. We also report an association between supernumerary teeth and TMDs that has not been reported earlier in the literature.